Carceral con : the deceptive terrain of criminal justice reform - Whitlock, Kay; Heitzeg, Nancy A. (University of California Press, 2021)
"From the beginning, evasions, hedging, deceptive rhetoric, trap doors, backroom reversals, hidden agendas, and slippery 'success' indicators have been built into the misleading and false promises of sweeping criminal justice reform. In the wake of the 2020 protests of racist structural violence, many people seek to better understand why contemporary reforms haven't produced more justice, especially justice for Black people. This book tells the story of the smoke-and-mirrors nature of those reform agendas and their ongoing failures to dismantle the entwined harms of structural racism and poverty so foundational to the criminal legal system. Carceral Con argues that it is not possible to fully grasp the implications of various reforms without inquiring more deeply into multiple forms of structural inequality and violence that are foundational to the United States and its systems of policing and carceral control. That is to say, racial, gendered, economic, and ableist hierarchies and discrimination are structured into the everyday workings of political, legal, and economic systems. Utilizing an abolitionist lens, this book asks readers to think differently about public safety, community well-being, and the purpose of justice. Chapters are organized to provide readers with basic information foundational to the subject, and then to follow the reform trail through the carceral funnel as most people are swept into the criminal justice system. Carceral Con encourages readers to make necessary paradigm shifts beyond the structures of racial capitalism and neoliberalism and to reject, or at least question, the notion that jails, prisons, and the policing that fill them are indispensable to the good society. Carceral Con also invites readers to reject reformism as an adequate response to the inequalities and brutality of the criminal legal system. Sometimes, as readers will see, it is better to withhold support, better to regroup and redefine the fight, than to embrace proposals that will make things worse"--